Success Guidelines: Proteksi Ruang Emosi dan Pikiran - Lia Fitriani; Masduki Asbari; Roy Cahya Wijaya (AGUSPATI RESEARCH INSTITUTA, 2023)
This study aims to find out guidelines for success. In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to the oral narrative from Helmy Yahya's YouTube channel, entitled